Channel islands in a reflective ocean large-scale eventdistribution in heterogeneous networks. - Crowcroft, J.
We discuss the design of a multicast event distribution service intended to support extremely large-scale event distribution. To date, event notification services have been limited in their scope due to limitations of the infrastructure. At the same time, Internet network and transport layer multicast services have seen limited deployment due to lack of user demand (with the exception of streaming services, e.g., on Sprint's US core network and in the Internet II). Research in active networks and reflective middleware suggests a way to resolve these two problems at one go. The goal of this article is to describe a reflective middleware system that integrates the network, transport, and distributed middleware services into a seamless whole. The system integrates this "low-level" technology into an event middleware system, suitable for telemetry, novel mobile network services, and other as yet unforeseen applications
Keywords: IETF; IP multicast; Internet; Internet Engineering Task Force; Internet II; Sprint US core network; Active networks; Distributed middleware services; Event middleware system; Event notification services; Heterogeneous networks; Large-scale event distribution; Mobile network services; Multicast event distribution service; Network services; Reflective middleware system; Streaming services; Telemetry; Transport layer multicast services